THE FOSSIL ASSEMBLAGE FEATURES OF LIMESTONE AND CLASTIC SEDIMENTARY ROCK IN LULUT AREA, CILEUNGSI DISTRICT, BOGOR, WEST JAVA - -, Vijaya Isnaniawardhani; -, Rusman Rinawan; -, Bambang Prianggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2012)
The geological mapping for limestone and clastic sedimentary rock in Lulut area was conducted. The study area was composed of claystone, siltstone, sandstone and limestone intercalations of Jatiluhur Formation formed within neritic setting in Middle Miocene age. This section interfingers with rich coral and algae limestone of Klapanunggal Formation.Larger foraminifera (Milliolids, Nummulites spp., Amphistegina spp., Operculina spp., Cycloclypeous spp.), globigerinids, calcareous red and green algae, corals, Molllucs and Brachiopods shell fragments were recorded in biogenic limestone. The marine invertebrata fossil assemblages (Molluscs, Brachiopods) as well as shallow marine trace fossils (skolithos, cruziana) were recorded in calcareous claystone, siltstone, sandstone and bioclastic limestone. Planktic and small benthic foraminifera assemblages were found in fine clastic sedimentary rock.The identified larger foram, globigerinids, coral and calcareous algae assemblages associated with invertebrate shell fragments can be indicated age and environmental of limestone. Based on the fossil assemblages and morphology characteristics of the study area, the limestone was formed in back-reef zones (northern part, at Bagogog-Cilalay); reef-crest (central part, at Pasir Bali, Kutalingkung, Sibancana, Kuari D); and fore-reef zones (southern part, at Cileungsi, Ciseah). In the southern part, claystone interlaminations and intercalations are commonly recorded. The reef complex grew in Tertiary age within neritic zone.Some index planktic foraminifera (Globigerinoides primordius, Globigerinoides ruber, Globorotalia continousa, Globorotalia siakensis, Globorotalia mayeri, Hastigerina siphonifera and Orbulina suturalis) recorded in carbonaceous clastic sedimentary rock indicated that sedimentary rock of Jatiluhur sections deposited within Middle Miocene Zones N.9 to N.14. Benthic and planktic foraminifera assembalges in the sections indicated that the sediments were deposited in neritic setting. This is supported by the appearance invertebrate fossils and trace fossils.